The legal protection of religious sentiments on the Internet: Freedom of speech vs hate speech - Aranda Serna, Francisco J. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The objective of this article is to analyze the legal conflict that exists between the fundamental right to express opinions and ideas, and the fundamental right that religious beliefs are protected from offenses in the social context of the Internet. Through the analysis of scientific articles, legislation and judicial sentences, the most relevant typical criminal figures will be determined, and through a study of European and North American comparative law, the keys will be extracted for a better delimitation of these rights.